Recent progress on photoluminescence from plasmonic nanostructures : phenomenon, mechanism, and application - Yin, Tingting (2020)
Photoluminescence (PL) from bulk noble metals arises from the interband transition of bound electrons. Plasmonic nanostructures can greatly enhance the quantum yield of noble metals through the localized surface plasmon. In this work, we briefly review recent progress on the phenomenon, mechanism, and application of one-photon PL from plasmonic nanostructures. Particularly, our recent efforts in the study of the PL peak position, partial depolarization, and mode selection from plasmonic nanostructures can bring about a relatively complete and deep understanding of the physical mechanism of one-photon PL from plasmonic nanostructures, paving the way for future applications in plasmonic imaging, plasmonic nanolasing, and surface enhanced fluorescence spectra.